Microalgal hydrogen production: prospects of an essential technology for a clean and sustainable energy economy - Bayro-Kaiser, Vinzenz (Photosynth Res, 2017)
Modern energy production is required to undergo a dramatic transformation. It will have to replace fossil fuel use by a sustainable and clean energy economy while meeting the growing world energy needs. This review analyzes the current energy sector, available energy sources, and energy conversion technologies. Solar energy is the only energy source with the potential to fully replace fossil fuels, and hydrogen is a crucial energy carrier for ensuring energy availability across the globe. The importance of photosynthetic hydrogen production for a solar-powered hydrogen economy is highlighted and the development and potential of this technology are discussed. Much successful research for improved photosynthetic hydrogen production under laboratory conditions has been reported, and attempts are underway to develop upscale systems. We suggest that a process of integrating these achievements into one system to strive for efficient sustainable energy conversion is already justified. Pursuing this goal may lead to a mature technology for industrial deployment.